Análise por planejamento fatorial da corrosão por pites de aços inoxidáveis duplex em altas concentrações de íons cloreto - Barce, Mariana Sanches (2012)
The duplex stainless steels UNS S32101 and UNS S31803, hot rolled, were chosen for the study of localized corrosion pitting for presenting interesting properties of mechanical strength and corrosion resistance for the petrochemical industry. The anodic potentiodynamic polarization test was conducted in aqueous solution with concentrations of chloride ions ranging from 30x103 to 250x103 ppm Cl- (LiCl), under 25°C and 40 ° C in an environment saturated with CO2 and aerated. The pitting potential and corrosion potential were statistically analyzed using factorial design 23. The observation of the microstructure and the pits formed were recorded with scanning electron microscopy (SEM). The results show that the decrease in corrosion potential was significantly influenced by the same factors in both steels: saturation with CO2 and the concentration of chloride anions, while the pitting potential was significantly influenced by different factors, depending on the steel used and the environmental conditions. Thus, the decrease in pitting potential of steel UNS S32101 was significantly influenced by temperature, concentration of chloride anions, interaction between these two parameters and saturation with CO2. On the other hand the decrease in pitting potential of the UNS S31803 steel was significantly influenced by chloride concentration, temperature and the interaction of each of these parameters with the saturation of the medium with CO2. Data analysis by statistical method of factorial design showed that not all studied factors affect localized corrosion significantly and that the effect of these factors is not cumulative.